THE INFLUENCE OF SERVICE QUALITY DIMENSIONS ON PATIENT LOYALTY WITH SATISFACTION AS A MEDIATING VARIABLE AT PKU MUHAMMADIYAH WONOGIRI HOSPITAL - Khusnul Khotimah Ariyani; Iwan Setiawan Adji; Soepatini (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the influence of service quality dimensions, including tangible, reliability, responsiveness, assurance, and empathy, on patient loyalty, with patient satisfaction as a mediating variable at PKU Muhammadiyah Wonogiri Hospital. This study employed a quantitative, survey-based approach. The sample consisted of 200 outpatients selected using purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. The results showed that reliability, assurance, and empathy had a positive and significant effect on patient satisfaction, while tangibles and responsiveness did not significantly influence satisfaction. Patient satisfaction had a positive and significant effect on patient loyalty. Furthermore, tangibles, assurance, and empathy had a direct significant effect on patient loyalty, while reliability and responsiveness did not show significant direct effects. The mediation analysis revealed that patient satisfaction significantly mediated the relationship between empathy and patient loyalty, while the mediating effect of satisfaction on the relationship between reliability and loyalty was weak or marginal. In contrast, satisfaction did not mediate the relationships between tangibles, responsiveness, or assurance and patient loyalty. These findings indicate that emotional and interpersonal aspects of healthcare services, particularly empathy, play a central role in enhancing patient satisfaction and loyalty. Therefore, hospitals are encouraged to strengthen healthcare worker–patient interactions to improve long-term patient loyalty.